Audit committee effectiveness and earnings conservatism : an Australian analysis - Sultana, Nigar (Curtin University, 2010)
The overarching objective of this study is to examine the association between audit committee effectiveness and the level of earnings conservatism exhibited by Australian publicly listed firms. Studying the audit committee effectiveness/earnings conservatism linkage is both important and timely given the deterioration in reported earnings by firms. This study measures audit committee effectiveness based on four prime components underlying its effectiveness (i.e., independence; financial expertise; experience; and diligence) and earnings conservatism is measured following Basu (1997) and Ball and Shivakumar (2005). Using a sample of 494 firm-year observations for the period 2004 to 2008, overall results show that there is no significant association between audit committee effectiveness and earnings conservatism. Further analysis, however, indicates that firms with audit committees comprising financially qualified, experienced and more diligent members are associated with higher earnings conservatism levels. Results from this study have wide-ranging implications for regulators, investors, firms/corporate management and scholars.